EXPERIMENTAL STUDY OF LAMINATION COLUMN WITH SEVERAL TYPES OF WOOD USING ADHESIVE NAILS AND BOLT - Indriyani Puluhulawa (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2019)
The use of light wood combined with heavy wood can improve the quality of the combinationwood. Apart from being used as laminated beams, a combination of light wood and heavy wood can also be used as a laminated column given compressive loads. Based on SNI 7973-2013, the adhesive that was permitted on built up columns or laminated columns can be in the form of bolts and nails, so this study has also used adhesive nails and bolts. This study purpose to determine the compressive capacity of the laminated column which combines several types of wood. The specimens made were four variations of the laminate column. Furthermore, three layers of wood have been used on one laminated column with heavy wood types on the outermost layer. The results showed that all variations of the laminated column had a higher compressive capacity than the solid column.Â Keywords: compressive capacity, lamination column, light and heavy wood